Converging Effects of Three Different Endocrine Disrupters on Sox and Pou Gene Expression in Developing Rat Hippocampus: Possible Role of microRNA in Sex Differences - Lichtensteiger, Walter; Bassetti-Gaille, Catherine; Rehrauer, Hubert; Georgijevic, Jelena Kühn; Tresguerres, Jesus A.F.; Schlumpf, Margret (Frontiers in Genetics, 2021)
Endocrine disrupters (EDCs) can impair hippocampus-dependent behaviors in rat offspring and in children. In search for key processes underlying this effect, we compared the transcriptomes of rat hippocampus on postnatal day 6, after gestational and lactational exposure to three different EDCs at doses impairing memory development, the PCB mixture, Aroclor 1254, and bisphenol A, both 5 or 0.5 mg/kg administered in chow, and chlorpyrifos, 3 or 1 mg/kg injected subcutaneously. Male hippocampus exhibited a common effect of all three chemicals on genes involved in cell-autonomous processes, Sox6, Sox11, Pou2f2/Oct2, and Pou3f2/Brn2, all upregulated at the high dose. Additional Sox genes and Pou2f1/Oct1 were affected by two treatments. Real time RT PCR showed a comparable expression change for bisphenol A also at the lower dose. No changes were seen in female hippocampus. Since gene network analyses suggested a link between Sox6 and miR-24, known to be repressed by activation of ER-alpha and to repress Sox6 in other tissues, this microRNA was measured. miR-24 was downregulated by all chemicals at the high dose in males, but unchanged in females. Individual values of Sox6 mRNA and miR-24 in males were inversely correlated, indicating direct interaction. Data suggest a role of miR-24 in sex dependency of treatment effects; microRNAs may be relevant for sexually dimorphic EDC actions. ER-alpha expression was sex-dependent. Sox6 suppresses differentiation of Pvalb-expressing interneurons. Individual Sox6 levels (FPKM) were inversely correlated with Pvalb, but not with markers of Sox6-independent interneuron subpopulations, Nos1 and 5HT3aR. Effects on interneuron development are further suggested, in males, by expression changes of Nrg1 and its receptor Erbb4, controlling interneuron migration. Our study disclosed new types of genes which, if corroborated by further experiments, may serve as markers of early developmental stages in regulatory test development.